The Differential Effects of Public and Private Active Social Media Use on Adolescents’ Well-Being: Insights from a Cross-Sectional and Experimental Study - Jing Qiao; Ming Ji (Behavioral Sciences, 2026)
While existing research on active social media use and well-being has yielded inconsistent findings, this study introduces a refined typology distinguishing between public (e.g., posting broadly on social networks) and private (e.g., one-on-one messaging) active use to clarify these effects. It further examines the moderating role of perceived online social support. Study 1 (N = 689) used a cross-sectional survey design to analyze the relationships among public versus private active social media use, perceived online social support, and well-being in a population of Chinese adolescents. Building upon these findings, Study 2 (N = 158) used a scenario-based experiment to further validate the findings of Study 1. Both studies found that public active social media use had a stronger effect on well-being than private active social media use. Perceived online social support moderated the relationship between public active social media use and well-being. Specifically, under the public active social media use condition, participants in the low online social support group were less likely to report well-being than those in the high online social support group. However, under the private active social media use condition, there was no difference between the high and low support groups. This study provides new insights into the relationship between active social media use and well-being. However, the moderation effect was modest in magnitude, and Study 2 relied on a single-item well-being measure; the directional conclusions should therefore be interpreted with appropriate caution.